2022
DOI: 10.3390/jintelligence10010003
|View full text |Cite
|
Sign up to set email alerts
|

How Is Cultural Intelligence Related to Human Behavior?

Abstract: Cultural intelligence is an individual’s ability to recognize, understand, and adapt to cross-cultural contexts in order to change his or her self-capacity. Hence, this study explores the relationship between cultural intelligence and interpersonal communication, psychological capital (PsyCap), and organizational citizenship behavior (OCB) among teachers in Indonesia and investigates the possibility of finding relevant new models. A Likert questionnaire was used to collect research data. The research participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…No articles were ranked in the core (motor) topic’s quadrant. This journal also showed three separate niched clusters indicating only few researchers used the keywords working memory and executive function (see Panesi et al 2022 ; Rosas et al 2022 ) cultural intelligence and the g -factor ( Alifuddin and Widodo 2022 ; Sternberg 2022 ; Sternberg et al 2022 ), and items carelessness and guessing ( Antoniou et al 2022 ; Sideridis and Alahmadi 2022 ). Figure 8 shows the thematic map of keywords in JOI.…”
Section: Resultsmentioning
confidence: 99%
“…No articles were ranked in the core (motor) topic’s quadrant. This journal also showed three separate niched clusters indicating only few researchers used the keywords working memory and executive function (see Panesi et al 2022 ; Rosas et al 2022 ) cultural intelligence and the g -factor ( Alifuddin and Widodo 2022 ; Sternberg 2022 ; Sternberg et al 2022 ), and items carelessness and guessing ( Antoniou et al 2022 ; Sideridis and Alahmadi 2022 ). Figure 8 shows the thematic map of keywords in JOI.…”
Section: Resultsmentioning
confidence: 99%
“…Some factors that have been identified in the existing literature have been classified into two categories: (a) intercultural experiences [8][9][10] and (b) personality traits [11][12][13]. However, it has also been indicated that these two factors may not be sufficient to explain the variance in CQ [3,5]. Regarding CQ closely related to the activities of the brain [14,15], elements of lifestyle could be considered as another possible antecedent of CQ because research in brain science has clarified the relationship between lifestyles and brain conditions [16][17][18], which indicates the consequent association between lifestyles and CQ.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognitive CQ reflects mental processes that individuals use to acquire and understand cultural knowledge; cognitive CQ reflects knowledge of the norms, practices, and conventions in different cultures acquired through education and personal experiences; motivational CQ reflects the capability to direct attention and energy toward learning about and functioning in situations characterized by cultural differences; and behavioral CQ reflects the capability to exhibit appropriate verbal and nonverbal actions when interacting with people from different cultures [3]. CQ has been linked to various skills and behaviors, including cultural adaptation and performance [4], organizational citizenship behavior [5], and work engagement [6].…”
Section: Introductionmentioning
confidence: 99%
“…Davidaviciene and Al Majzoub (2022) discovered that CQ has a positive effect on the decision-making processes in virtual teams operating in the Middle East. Alifuddin and Widodo (2022) examined the relationship between cultural intelligence and interpersonal communication, psychological capital, and organizational citizenship behavior on a sample of 450 Indonesian junior high school teachers and found that CQ is significantly related to all these factors.…”
Section: Cultural Intelligencementioning
confidence: 99%